INTRODUCTION: POSSIBILITIES, FUTURES, AND QUEER WORLD-MAKING IN CHILD AND YOUTH CARE - Vachon, Wolfgang; Walker, Mattie (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
In this introduction, the authors situate this special issue within the current sociopolitical contexts of child and youth care (CYC) and offer potentialities through “queering CYC”. They consider how CYC might be analyzed through a queered lens, outline ways CYC has, and has not, taken up queer theory, and imagine what a queered CYC might (un)become. The authors provide context for this issue and invite queer generosity in reading how queering can be in conversation with CYC.